Analysis of Sodium Benzoate Levels in Commercial Jellies and Jams using High-Performance Liquid Chromatography (ALKIMIA : Jurnal Ilmu Kimia dan Terapan, 2023)
The use of food additives, when posing minimal risk to human health, is generally considered acceptable, as it is a common practice in food production. Among the commonly used food additives are preservatives. Benzoate compounds are frequently employed as preservatives in food products, with sodium benzoate being a prominent example. Sodium benzoate is a synthetic benzoate compound often preferred as a preservative due to its higher solubility when incorporated into food. This study was conducted at Balai BPOM to analyze the sodium benzoate content in commercial jellies and jams. Four samples of jelly and jam were analyzed for sodium benzoate content using High-Performance Liquid Chromatography (HPLC). Two samples (codes 313 and 321) tested positive for sodium benzoate, while the other two (codes 294 and 311) tested negative. The sodium benzoate content in samples 313 and 321 was determined to be 179.10 mg/kg and 165.35 mg/kg, respectively. Based on PerBPOM No. 11 of 2019, both samples were declared safe for consumption.